Decolonization of Arctic Library and Archives Metadata (DALAM) Thematic Network Update: October, 2023 – April, 2024 - Campbell, Sandy (2024)
This article reports activities of the University of the Arctic Decolonization of Arctic Library and Archives Metadata (DALAM) Thematic Network for October 2023 - April 2024.